Does leucocytosis identify bacterial infections in febrile neonates presenting to the emergency department?. Issue 4 (23rd March 2005) - Brown, L; Shaw, T; Wittlake, W A
Abstract : Objective: This study was undertaken to evaluate the discriminatory power of the peripheral white blood cell (WBC) count to identify bacterial infections in a cohort of febrile neonates (⩽28 days of age) presenting to an emergency department. Methods: Retrospective medical record review using descriptive statistics and a receiver operating characteristic (ROC) curve. Neonates who presented to a tertiary care paediatric emergency department between 1 January 1999 and 22 August 2002, had a temperature ⩾38°C, underwent lumbar puncture, and had a WBC count obtained were included. They were divided according to microbiological and radiographic findings into four groups: bacterial infections, viral infections, pneumonia, and negative sepsis evaluations. Results: A total of 69 febrile neonates met the inclusion criteria. The number of neonates in each group was as follows: 8 with bacterial infections, 10 with viral infections, 3 with pneumonias, and 48 with negative sepsis evaluations. There was substantial overlap in WBC counts among the groups. The area under the ROC curve was 0.7231 (95% CI 0.5665 to 0.8797). Conclusion: In a cohort of febrile neonates evaluated in the emergency department, the WBC count had modest discriminatory power in identifying neonates with bacterial infections and demonstrated substantial overlap among groups. The present data suggest against the use of any WBC count threshold to identify bacterial infections in febrile neonates presenting to the emergency department.